The territory of Japan its history and legal basis - Serita, Kentar?o; Meyer, Alex (Translator); Serita, Kentar?o. (2018)
"The Northern Territories, Takeshima, and the Senkaku Islands--what exactly is the territorial extent of Japan? To answer this fundamental question, the author, an authority on international law, retraces and analyzes the history of negotiations over these territories, while also setting forth his vision of the future of issues concerning territorial land, air, and sea"--Dust jacket.
Development of Japan's territory -- The northern territories (Kunashiri Island, Etorofu Island, Habomai Islands, and Shikotan Island) -- The Senkaku Islands -- Takeshima -- Territorial sea and exclusive economic zone -- Exclusive economic zones between Japan and the Republic of Korea, and Japan and China -- A proposal for stability and coexistence in East Asia -- Territorial air space and air defense identification zones -- Epilogue.
Translation of: Nihon no ry?odo.
Originally published in Japanese by Chuokoron-Shinsha, Inc. in 2010, revised from the original 2002 edition, published by the same publisher.
Includes bibliographical references (pages 257-261)
Japan Foundation
In English; colophon also in Japanese.
Keywords: Territory, National -- Japan -- History; Islands -- Law and legislation; Economic zones (Law of the sea); Continental shelf; Territorial waters